Relationship between stressful life events with the development of breast cancer - Bartków, Aleksandra; Ananicz, Bogumiła; Sieja, Krzysztof; Stanosz, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2002)
Breast cancer as a neoplasm associated with neurohormonal and immunological systems is probably one of the neoplasms being most susceptible to the influence of stressful life events. The course of stress reaction and the mechanisms by which the stress influences the physiological functions were presented. Critical life events causing difficulties in the readjustment are termed stressful life events. On the social adjustment scale - the first items in the average points rating appeared to be the deaths of the spouse or child, divorce, separation, imprisonment, the death of close family member, own trauma or disease. In many papers the bereavement falls into the severe life events categories. Bereavement of close person is often use to measure psychological stress. In one part of the cited works the relationship between stressful life events and breast cancer was disclosed. However in other part the hypothesis as to the existence of relationship between psychological stress and the incidence of breast cancer was not confirmed. The above finding may be linked with insufficient methodological elaboration of these investigations. Although the range of findings concerning the relationships between stress and the occurrence of breast cancer is limited due to the mode of measuring the life events, the risk of subsequent diagnosis of breast cancer may be related with: 1) the number of cumulated life events being experienced by the subject, 2) the extent of stress perceived by the subject, 3) experiencing of defined type of stress. The authors point out the special attention the role of markers of stress (adrenaline, noradrenaline, prolactin, cortisol) in the etiopathogenesis of breast cancer and the mechanisms by which stress has negative influence on psychophysical function, neuroendocrine (the axis: limbic system-hypothalamus-hypophysis-adrenals) and immunological systems. The results of a number of experimental references indicated on promoted influence of the stress reaction on the carcinogenesis processes. The stress accelerate the spread of breast cancer metastases. It is possible, that the factor responsible for this state may be the immunosuppressive influence of certain parts of stress reaction e.g. corticosteroids. In order to elucidate the way in which the individual, specific stressful life events, particularly bereavement, may influence the occurrence of the cancer the authors of this work suggest the connection of studies involving psychological examination and biological mechanisms (stress markers) demanding a close cooperation between the psychologists and physicians. The full confirmation and wider appreciation of the hypothesis concerning the relation between stressful life events with breast cancer will allow us to declare the women affected by these events, particularly bereavement as a "risk group" exposed to the development of breast cancer.